KONTRIBUSI FILSAFAT PENDIDIKAN KONSTRUKTIVISME JEAN PIAGET BAGI PENDIDIKAN MODERN - Blasius Helyanan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2026)
This article aims to provide a philosophical analysis of constructivist education in Jean Piaget’s thought and to examine its relevance to contemporary educational practice. The main problem addressed is the persistence of mechanistic learning models that overlook the internal process of knowledge construction and the cognitive developmental stages of learners. This study employs a library research method with a phenomenological-philosophical approach through critical analysis of Piaget’s major works and relevant literature in philosophy of education and developmental psychology. The findings reveal that Piagetian constructivism positions learners as active subjects who construct knowledge through assimilation, accommodation, and equilibration in accordance with cognitive development. Learning is thus understood as a process of adaptation and meaning-making rather than mere knowledge transmission. Although Piaget’s theory significantly contributes to learner-centered education, it requires integration with social and emotional dimensions. The relevance of this study lies in strengthening the philosophical foundation of humanistic and reflective education.